PERAN WAYFINDING DALAM ARSITEKTUR: ANTARA FUNGSI DAN ESTETIKA - Muhammad Fathur Hidayat; Agung Budi Sardjono2 (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2026)
Abstract: Wayfinding is an important concept in architecture that relates to an individual's ability to find direction and purpose in the physical environment, whether familiar or unfamiliar. The concept not only emphasizes functional aspects as a navigation tool, but also contains aesthetic dimensions that enrich the user's experience of the space being traversed. As architectural design develops and the complexity of modern public spaces increases, the role of wayfinding becomes increasingly crucial to ensure the comfort, safety and efficiency of user mobility in various types of buildings, such as stations, airports, museums, hospitals, shopping centers and other public facilities. This research uses a descriptive qualitative method with a literature study and case study approach to examine in depth the integration of navigation functions and aesthetic values in architectural wayfinding systems. Data were collected from various literature sources as well as observations of buildings that implement wayfinding, both highlighting functional and aesthetic aspects. The results show that an effective wayfinding system not only provides clear and intuitive directional information through signage, circulation paths, colors and landmarks, but is also able to strengthen the visual identity of the building through the design of aesthetic elements that are harmonious with the architecture. Case studies of the Guggenheim Museum in New York and the U District Station in Washington demonstrate the application of wayfinding that successfully combines navigation functions with aesthetic values, both through communicative space design and the use of strategic and visually appealing signage. Thus, the integration of function and aesthetics in wayfinding is both a challenge and an opportunity for architects and designers to create a built environment that is not only functional, but also aesthetic and comfortable for all users. Keyword: Wayfinding System, Wayfinding Function, Wayfinding Aesthetics Abstrak: Wayfinding merupakan konsep penting dalam arsitektur yang berkaitan dengan kemampuan individu untuk menemukan arah dan tujuan di lingkungan fisik, baik yang familiar maupun asing. Konsep ini tidak hanya menekankan aspek fungsional sebagai alat navigasi, tetapi juga mengandung dimensi estetika yang memperkaya pengalaman pengguna terhadap ruang yang dilalui. Seiring berkembangnya desain arsitektur dan meningkatnya kompleksitas ruang publik modern, peran wayfinding menjadi semakin krusial untuk memastikan kenyamanan, keamanan dan efisiensi mobilitas pengguna di berbagai jenis bangunan, seperti stasiun, bandara, museum, rumah sakit, pusat perbelanjaan dan fasilitas publik lainnya. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan studi literatur dan studi kasus untuk mengkaji secara mendalam integrasi fungsi navigasi dan nilai estetika dalam sistem wayfinding arsitektur. Data dikumpulkan dari berbagai sumber pustaka serta pengamatan terhadap bangunan yang menerapkan wayfinding, baik yang menonjolkan aspek fungsional maupun estetika. Hasil kajian menunjukkan bahwa sistem wayfinding yang efektif tidak hanya memberikan informasi arah secara jelas dan intuitif melalui signage, jalur sirkulasi, warna dan landmark, tetapi juga mampu memperkuat identitas visual bangunan melalui desain elemen yang estetis dan harmonis dengan arsitektur. Studi kasus pada Museum Guggenheim di New York dan Stasiun U District di Washington memperlihatkan penerapan wayfinding yang berhasil menggabungkan fungsi navigasi dengan nilai estetika, baik melalui desain ruang yang komunikatif maupun penggunaan signage yang strategis dan visual menarik. Dengan demikian, integrasi fungsi dan estetika dalam wayfinding menjadi tantangan sekaligus peluang bagi arsitek dan desainer untuk menciptakan lingkungan binaan yang tidak hanya fungsional, tetapi juga estetis dan nyaman digunakan oleh seluruh pengguna. Kata Kunci: Sistem Wayfinding, Fungsi Wayfinding, Estetika Wayfinding